PENINGKATAN PENGETAHUAN IBU HAMIL MEMILIH OBAT BEBAS MENGGUNAKAN METODE CBIA (CARA BELAJAR INSAN AKTIF) - Musdalipah; Mulyadi Prasetyo; Moldefya Wahid Ado (JIIS: Jurnal Ilmiah Ibnu Sina, 2016)
Community Based Interactive Approach (CBIA) was a society learning method which was be oriented to an active role of the students in search of the information and grow critical attitude and alter behavior. The purpose of this study was to determine the improvement of pregnant woman’s knowledge in choosing a drug-free by using CBIA method. The study was conducted at the Perumnas health center of Kendari city in period May to July 2016. The study was a quantitative pre-experimental design with one-group pretest-posttest. The number of samples in this study were 30 respondents. Pretest initial test conducted by distributing questionnaires, then the extension services provided by the facilitator, and tested again by posttest questionnaire. Data were analyzed statistically with Mc Nemar test. The results showed the pretest, respondents who have good knowledge categories of 6 people (20%) and less categories of 24 people (80%). At posttest increased knowledge that respondents who have a good knowledge of the category of 20 people (66.67%) and less than about 10 people (33.33%). The result Mc Nemar test obtained by value p = 0.0001 (<0.005) showed that there was a significant relationship CBIA methods to improvement of pregnant woman’s knowledge in choosing a drug-free at the Perumnas health center of Kendari city.